Scalable 3D Printed Molds for Human Tissue Engineered Skeletal Muscle - Capel, Andrew J.; Rimington, Rowan P.; Fleming, Jacob W.; Player, Darren J.; Baker, Luke A.; Turner, Mark C.; Jones, Julia M.; Martin, Neil R. W.; Ferguson, Richard A.; Mudera, Vivek C.; Lewis, Mark P. (Frontiers in Bioengineering and Biotechnology, 2019)
Tissue engineered skeletal muscle allows investigation of the cellular and molecular mechanisms that regulate skeletal muscle pathology. The fabricated model must resemble characteristics of in vivo tissue and incorporate cost-effective and high content primary human tissue. Current models are limited by low throughput due to the complexities associated with recruiting tissue donors, donor specific variations, as well as cellular senescence associated with passaging. This research presents a method using fused deposition modelling (FDM) and laser sintering (LS) 3D printing to generate reproducible and scalable tissue engineered primary human muscle, possessing aligned mature myotubes reminiscent of in vivo tissue. Many existing models are bespoke causing variability when translated between laboratories. To this end, a scalable model has been developed (25-500 μL construct volumes) allowing fabrication of mature primary human skeletal muscle. This research provides a strategy to overcome limited biopsy cell numbers, enabling high throughput screening of functional human tissue.